Weathering and erosional processes within the landslide deposit of Jarlang (Ganesh Himal), central Nepal - Uhlir, C. F.; Schramm, J. M. (Journal of Nepal Geological Society, 1997)
Within the southern flanks of the Ganesh Himal in central Nepal, an area of complex landslides lies in the Jarlang area, situated at the southeastern slope of the Ankhu Khola valley. Slow rotational rockslide in deeply weathered micaceous quartzites interlayering with mica schists have destabilized the head scarp composed of augen gneiss. It caused rockslides from the main scarp generating big spread-out landslides. The landslides of Jarlang generated a stratified deposit (> 106 m3) of matrix-poor breccias with thin fine grained shear horizons. The initial event for the biggest gully system in central Nepal was a gravitational slump owing to nine, day heavy rainfall in 1954. The recent processes within these colluvial deposits are torrential gully erosion accompanied by successive rotational and translational slides along the gully margins. The high activity within the Jarlang gully system can be explained by reactivation of the old Jarlang landslide's shear horizons. The slide grew from an original width of 300 m to 1.2 km at present, covering an area of 2.68 km2. The total volumetric loss by 1996 is l.46xl08 ml. The triggering factor for rock slides and rock falls generating big spread out landslides and debris slides and slope undercutting is seismic events due to extremely high uplift of the Himalayan Orogeny. The strong influence of human activities on slope stability and mass wasting as proposed in the Himalayan Environmental Degradation Theory can not be validated.